THE RELATIONSHIP BETWEEN RELIGIOSITY AND EMOTIONAL REGULATION IN HIGH SCHOOL (SMA) STUDENTS IN BANDA ACEH - Bustamam, Nurbaity; Nisyah, Cut Chairun; Nurhasanah, Nurhasanah (Fakultas Psikologi, Universitas Islam Negeri (UIN) Ar Raniry Banda Aceh, 2024)
Emotional regulation is a way to assess, deal with, manage and express emotions in certain situations. The factor that influences emotional regulation in individuals is religiosity. A person who has religiosity involves religion in behaving and taking action, so that it has an effect on controlling his emotions. This research aims to describe religiosity and emotional regulation, as well as to see the relationship between religiosity and emotional regulation in high school students. Research respondents involved 364 students selected from five high schools in Banda Aceh City. Samples were collected using random sampling techniques with the Slovin formula, data collection used a Likert scale of religiosity and emotional regulation. The research results show that the correlation coefficient (r) between the variables studied is 0.721, which indicates a strong correlation between religiosity and emotional regulation. This finding can be interpreted as the higher the religiosity, the higher the student's emotional regulation and vice versa.